UJI PERENDAMAN KOMBINASI LARUTAN TEPUNG KUNYIT DAN CACING SUTERA (Tubifex sp) TERHADAP SINTASAN DAN PERTUMBUHAN BENIH IKAN BAUNG (Hemibagrus nemurus) - Muhammad Hasby; T. Iskandar Johan; Akbar Antoni (UIR Press, 2022)
This study aims to determine the effect of the long soaking of silkworms (Tubifex sp) in turmeric flour solution on the dilution and growth of baung fish fry (Hemibagrus nemurus). The method used is a Complete Randomized Design (RAL) with 5 treatments of 3 tests, namely P0 treatment = no soaking, P1 = Soaking for 20 minutes, P2 = 25 minutes, P3 = 30 minutes and P4 35 minutes. The baung fish used are fry that are 8 days old with an average weight of 0.09 gr / tail with a length of 0.70 cm / tail. The seeds were obtained from Saprizal's UPR in Padang Mutung village, Kampar district. From the results of the study, the highest dilution was obtained in the P4 treatment by 100% and the lowest in P0 by 97.33%. The highest absolute weight growth of P4 treatment was 0.57 gr and the lowest was 0.37 gr. The highest absolute length growth in the P4 treatment was 3.46 cm and the lowest was 2.99 cm. The highest daily growth rate of P4 treatment was 0.08% and the lowest was 0.05%. The best feed conversion value is P4 treatment of 0.463%. Water quality parameters are temperature 28-30 0C, pH 6.13-7.69, dissolved oxygen 3.4-6.3 mg/L and Ammonia 0.88-4.22 mg/L.